Performance enhancement in proton exchange membrane water electrolyzers through the metal foam flow fields with orderly arranged pore structure - Li Zhan; Shihao Lin; Qihao Deng; Wenshang Chen; Yi Yu; Guangfu Li; Ben Chen (Fuel, 2026)

Synthesis of NiFe-Fc-MOF/LDH/NF with tip effect enhancing electric field for oxygen evolution reactions - Xiangyu Meng; Liang Ma; Zengyan Wei; Jia Song; Fengqi Zhang; Shihao Wu; Mo Yan; Bo Chen; Lin Zhu; Dechang Jia; Yu Zhou; Xiaoming Duan (Chemical Engineering Journal, 2026)

Direct recovery of silver and simultaneous purification of silicon from end-of-life photovoltaic modules via a one-step hydrothermal method - Danyan Qin; Kai Zhang; Shihao He; Xian Xie; Jie Liu; Long Peng; Yingzhu Li; Di Wu; Yaokai Zhong; Yun Shen; Xianbao Wang; Liangyou Lin (Chemical Engineering Journal, 2026)

Novel insights into the effects of co-heat treatment versus pre-heat on the interaction between rice glutelin and aroma compounds - Lin Zhu; Mengke Zheng; Jing Li; Zhaodong Zhu; Shihao Sun; Donghao Zhang; Jihong Wu (Food Hydrocolloids, 2026)

Reforming trade governance for sustainable resource flows: Ecologically unequal exchange in Pan-Eurasia - Jiahui Li; Lin Huang; Jun Zhai; Shihao Wang (Environmental Impact Assessment Review, 2026)

Cottonseed protein as a sustainable alternative plant protein: Basic characteristics, recent advancements, applications and limitations - Xinjie Shang; Shu Li; Shiyu Lin; Shihao Sun; Li Liang; Yuyu Zhang; Rui Yang (Trends in Food Science & Technology, 2026)

From foe to friend: Taming the δ-phase of FAPbI3 for oriented growth and high-performance perovskite solar cells - Xian Xie; Yanzhuo Gou; Kai Zhang; Wei Zhang; Jiaqi Zhang; Jie Liu; Shihao He; Jinhua Li; Xianbao Wang; Liangyou Lin (Chemical Engineering Journal, 2026)

CHAPS-involved chitooligosaccharide glycosylation of ferritin cage for encapsulation of bioactive molecule by a mild process - Junrui Ma; Runxuan Chen; Chang Liu; Shiyu Lin; Chunkai Gu; Lingling Zhang; Ruge Cao; Fang Wang; Demei Meng; Shihao Sun; Yuyu Zhang; Rui Yang (Food Chemistry, 2025)

Monocyte/macrophage-mediated transport and intratumoral bacteria-responsive ZIF nanoplatform for enhanced immunotherapy against microsatellite-stable colorectal cancer - Xietao Ye; Yeyang Sun; Lin Yang; Chen Chen; Shihao Li; Shuo Dong; Xiaoying Qin; Xiaoqi Li; Congyan Liu; Jiege Huo; Yuping Liu; Yan Chen (Chemical Engineering Journal, 2025)

Phenotypic and functional characterization of CD4-2+ T cells in large yellow croaker Larimichthys crocea - Xinran Li; Guolong Lai; Yan Lin; Sichang Liu; Wenbing Bao; Wenxuan Zhang; Li Huang; Guangming Shao; Shihao Chen; Yang Ding; Xinhua Chen (Fish & Shellfish Immunology, 2025)

Fisetin Augments OEC Neuroprotection Through Modulating Neurotrophin/Cytokine Signaling and Activating PI3K/Akt/CREB Pathway in an In Vitro Neurodegenerative Injury - Yizhen Jiang; Jianbin Guo; Yan Yang; Lin Li; Peng Deng; Shihao Yuan; Jinchao Wang; Hao Hui; Hao Yang (NeuroMolecular Medicine, 2025)

Mapping a High-Resolution Anthropogenic CO2 Emissions Inventory at City-Level Using Point-Line-Area Method - Shengxiang Liu; Wenbin Zhang; Qixiang Cai; Xiaohui Lin; Shihao Zhang (Aerosol Science and Engineering, 2025)

Topology design of two dimensional viscoelastic phononic crystals for wave attenuation based on deep generative neural networks - Jingru Li; Jingming Yin; Wei Lin; Zhifu Zhang; Shihao Liu; Xiaojuan Ma; Qingfen Ma (Engineering Structures, 2025)

Green solvent hydrothermal recycling of end-of-life crystalline silicon photovoltaic modules - Kai Zhang; Shihao He; Danyan Qin; Xian Xie; Wei Zhang; Pan Deng; Jintao Li; Hongdan Rao; Heming Deng; Tao Mei; Xianbao Wang; Liangyou Lin (Chemical Engineering Journal, 2025)

Apex ambition: Environmental management system certification in Chinese business groups - Shihao Yin; Zhongguo Lin; Binbin Peng; Qiang Ji; Huibin Du (Journal of Environmental Management, 2025)

In-situ transformation and synergistic electrocatalysis of asymmetric threefold hollow sites in rosebud-like ternary metal diselenide - Shihao Wang; Lin Liao; Jinsong Wu; Haolin Tang; Haining Zhang (Chemical Engineering Journal, 2025)

Landscape Stability Assessment and Simulation Analysis Under Urban Expansion: A Case Study of Hangzhou, China - Hui Pei; Lin Zhang; Minli Zhou; Wenbin Nie; Shihao Zhou; Yan Shi; Jianyun Pan (Chinese Geographical Science, 2025)

An experimental study on the morphology and behaviors of fire with nearby inclined surface during flame spread on building integrated photovoltaic (BIPV) - Yifan Lin; Yong Jiang; Shihao Li; Zhiyuan Zhang; Ying Zhang (Fuel, 2025)

Memory Reconsolidation Updating in Substance Addiction: Applications, Mechanisms, and Future Prospects for Clinical Therapeutics - Shihao Huang; Xiaoxing Liu; Zhonghao Li; Yue Si; Liping Yang; Jiahui Deng; Yixiao Luo; Yan-Xue Xue; Lin Lu (Neuroscience Bulletin, 2025)

Antimicrobial cyclic lipopeptides from Bacillus mojovensis B1302 against wheat root rot - Yanjie Yi; Shijie Liu; Shihao Ren; Yunpeng Shen; Xinyue Lin; Jia Shi; Kang Wang; Changfu Zhang (Rhizosphere, 2024)

Spatial distribution and risk assessment of heavy metal pollution from enterprises in China - Huading Shi; Shihao Wang; Xinliang Xu; Lin Huang; Qingbao Gu; Hanbing Liu (Journal of Hazardous Materials, 2024)

Structural characterization and prebiotic activity evaluation of novel fucosylated disaccharides prepared from bacterial exopolysaccharides - Shihao Nan; Xinmiao Ren; Mengshi Xiao; Lin Zhu; Haijin Mou; Ningyang Li; Rong Li; Shaoping Nie; Xiaodan Fu (Food Bioscience, 2024)

Hydrogel for bone microenvironment: Strategy and application - Guangfeng Li; Dongyang Zhou; Shihao Sheng; Qiushui Lin; Yingying Jing; Xiaoxiang Ren; Jiacan Su (Chemical Engineering Journal, 2024)

Multi-deformable interpenetrating network thermosensitive hydrogel fluorescent device for real-time and visual detection of nitrite - Lingfei Li; Dan Lin; Shihao Xu; Liang Yang; Changlong Jiang (Journal of Hazardous Materials, 2024)

Electrogenerated singlet oxygen and reactive chlorine species enhancing volatile fatty acids production from co-fermentation of waste activated sludge and food waste: The key role of metal oxide coated electrodes - Qingshan Lin; Shihao Xi; Boyi Cheng; Jinqi Jiang; Feixiang Zan; Yuanzhe Tang; Yeqing Li; Samir Kumar Khanal; Zongping Wang; Guanghao Chen; Gang Guo (Water Research, 2024)

Ultrasoft bioadhesive hydrogel as a versatile platform for the delivery of basic fibroblast growth factor to repair traumatic brain injury - Bixin Shen; Junhui Wang; Tao He; Shihao Chen; Xue Wang; Jun Chen; Ruiqing Shi; Jing Wang; Hao Wang; Wenting Huang; Chengkun Cao; Xianxi Tan; et al. (Chemical Engineering Journal, 2024)

Encapsulation of lutein in gelatin type A/B-chitosan systems via tunable chains and bonds from tweens: Thermal stability, rheologic property and food 2D/3D printability - Hongxia Wang; Xianyou Lin; Juncheng Zhu; Yuxin Yang; Shihao Qiao; Bo Jiao; Liang Ma; Yuhao Zhang (Food Research International, 2023)

Short-chain fatty acid production and phosphorous recovery from waste activated sludge via anaerobic fermentation: A comparison of in-situ and ex-situ thiosulfate-assisted Fe2+/persulfate pretreatment - Boyi Cheng; Da Zhang; Qingshan Lin; Shihao Xi; Jie Ma; Feixiang Zan; Basanta Kumar Biswal; Zongping Wang; Gang Guo (Science of The Total Environment, 2023)

A Strecker-like reaction triggering fluorescent sensing platform for enzyme-free and visual quantitative monitoring of carbamates - Lingling Qin; Jie Cao; Dan Lin; Shihao Xu; Yucheng Li; Changlong Jiang (Chemical Engineering Journal, 2023)

Optimizing waste activated sludge disintegration by investigating multiple electrochemical pretreatment conditions: Performance, mechanism and modeling - Qingshan Lin; Xinlei Dong; Shihao Xi; Boyi Cheng; Feixiang Zan; Jie Ma; Xiaoming Liu; Tianwei Hao; Gang Guo (Science of The Total Environment, 2023)

A 90-Day Prognostic Model Based on the Early Brain Injury Indicators after Aneurysmal Subarachnoid Hemorrhage: the TAPS Score - Runting Li; Fa Lin; Yu Chen; Junlin Lu; Heze Han; Li Ma; Yahui Zhao; Debin Yan; Ruinan Li; Jun Yang; Shihao He; Zhipeng Li; et al. (Translational Stroke Research, 2023)

Origins of black carbon from anthropogenic emissions and open biomass burning transported to Xishuangbanna, Southwest China - Xuyan Liu; Siwen Wang; Qianqian Zhang; Chunlai Jiang; Linlin Liang; Shihao Tang; Xingying Zhang; Xiuzhen Han; Lin Zhu (Journal of Environmental Sciences, 2023)

Hydrogen-bond induced enhanced emission ratiometric fluorescent handy needle for visualization assay of amoxicillin by smartphone sensing platform - Lingfei Li; Liang Yang; Dan Lin; Shihao Xu; Chunsheng Mei; Shaoming Yu; Changlong Jiang (Journal of Hazardous Materials, 2023)

Biofouling characteristics in Xinghua Bay of Fujian, China - Heshan Lin; Yaqin Huang; Yingyue Lin; Shuyi Zhang; Shihao Yu; Kun Liu; Jianfeng Mou; Junhui Lin; Xuebao He; Sujing Fu; Weijie Xie; Zhongbao Li (Frontiers in Marine Science, 2023)
Biofouling is one of the main factors affecting the efficiency and safety of cooling water systems in coastal nuclear power plants. Understanding the population dynamics, succession rules and cumulative effects of major fouling organisms is the basis for targeted prevention and control. A 1-year simulated concrete panel test was conducted from December 2020 to November 2021 in Xinghua Bay, China. A total of 78 species of fouling organisms were recorded by combining the monthly, seasonal, semiannual, annual and monthly cumulative panels, and the community composition was dominated by nearshore warm-water species, making for a typical subtropical inner bay-type community. The fouling organisms had a peak attachment period from June to October. Significantly more attachment was observed during summer (from June to August) than during the other three seasons. The attachment amount in the second half-year (from June to November) was much higher than that in the first half-year (from December to May). The attachment thickness, density, and biomass of the bottom summer panels reached 20 cm, 105,150 ind./m 2 , and 19,274.50 g/m 2 , respectively, while those of the bottom annual panels were 40 cm, 27,300 ind./m 2 , and 17,762.50 g/m 2 , respectively. The dominant fouling organisms with calcified shells mainly included Amphibalanus reticulatus and Pernaviridis . These species had high attachment amounts,could accumulate attachments for a long time, and even might cause secondary blockage, making them the most detrimental to the safety of a cooling system. Moreover,the seasonal upward growth of hydroids and bryozoans can also significantly reduce the efficiency of cooling water intake. We suggest that targeted prevention and control should be carried out according to the larval attachment period of different dominant groups of fouling organisms during June-October, which can greatly improve the prevention and control efficiency. Strengthening the research on the biological cycle phenomenon of the main species and their main environmental impact factors, and establishing a scientific and effective early-warning model are the governance direction of formulating and implementing scientific pollution prevention and control in the future.

Enhancing anaerobic fermentation of waste activated sludge by investigating multiple electrochemical pretreatment conditions: Performance, modeling and microbial dynamics - Shihao Xi; Xinlei Dong; Qingshan Lin; Xiang Li; Jie Ma; Feixiang Zan; Basanta Kumar Biswal; Mukesh Kumar Awasthi; Zongping Wang; Guanghao Chen; Gang Guo (Bioresource Technology, 2023)

Spatio-temporal variations in ecological spaces and their ecological carrying status in China’s mega-urban agglomerations - Shihao Wang; Lin Huang; Xinliang Xu; Jiahui Li (Journal of Geographical Sciences, 2022)

Influence of salinity on the biological treatment of domestic ship sewage using an air-lift multilevel circulation membrane reactor - Yuhang Cai; Asad A. Zaidi; Yue Shi; Kun Zhang; Xin Li; Shihao Xiao; Aqiang Lin (Environmental Science and Pollution Research, 2019)